The Influence of Influencer Reviews and Customer Reviews on Purchase Intention on Larissa Products - Sintya Oktarina; Firda Nisafera Ulfa; Dheny Indra Gunawan (Sean Institute, 2024)
In the contemporary globalized era, the advancement of internet technology has had a profound effect on business and the economy. The marketing reach, transaction speed, and speed of delivery of goods and services have all increased with the usage of internet technology in business. This demonstrates the wide range of categories of beauty and body care products available on the online store. The beauty business observes that consumer and influencer evaluations are two methods that electronic communication through word-of-mouth influences in order to promote and stimulate product purchase transactions. With the trust variable acting as a moderator, the purpose of this study is to quantify the direct impact of electronic word-of-mouth, including influencer and customer endorsements and reviews, on intentions to purchase Laresa products. This study employed a quantitative approach, which is a kind of causal investigation. In this study, convenience sample with 200 respondents was employed in place of nonprobability sampling. An ordinal scale questionnaire is used in this study's data collection and analysis processes. The study findings indicate that while influencer evaluations do not significantly positively impact the intention to purchase Laresa items, customer reviews do have a large beneficial affect. The association between customer reviews and the intention to buy Laresa items is negatively mediated by trust, however the relationship between influencers is not mediated by trust. assessment of the plan to buy products from Laresa.